Analysis of the Causes of Stunting in Toddlers in the Work Area of Gandasuli Community Health Center South Halmahera Regency North Maluku (Qualitative Study) - Osnawati H. Marsaoly; Nurwijayanti Nurwijayanti; Rahmania Ambarika; Sri Kardjati Maria (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Stunting is a linear growth disorder that is not appropriate for age indicating a long-term event and is an accumulative impact of insufficient nutrient consumption, poor health conditions and inadequate care. This study aims to analyze or explore in depth the causes of stunting in toddler. The research was conducted in the working area of ​​Puskesmas Gandasuli Kab. Halmahera Selatan, North Maluku. This research is a qualitative research with a sampling of researchers using non-probability sampling techniques, or rather researchers using purposive sampling technique. Subjects were determined based on inclusion criteria and obtained as many as 12 toddlers over 24 months. Data analysis in qualitative research is presented based on the data that has been collected and then conclusions are drawn. The results showed that the knowledge about stunting was still lacking, children were not exclusively breastfed causing malnutrition, errors in giving complementary foods which resulted in stunting, low family economic factors, inadequate use of posyandu, as well as poor environmental sanitation, food taboo culture for pregnant women, breastfeeding women and toddlers themselves so they can reduce their food intake which in turn reduces their nutritional status.